Hydrogen-bridged bis(silylene) complexes of ruthenium and iron: synthesis, structures and multi-centre bonding interactions at the M–Si–H–Si four-membered ring. Issue 27 (17th March 2017) - Hashimoto, Hisako; Komura, Katsuto; Ishizaki, Takatoshi; Odagiri, Yuto; Tobita, Hiromi
Abstract : Ruthenium and iron complexes featuring a MSi2 H four-centre bonding interaction were synthesized and the interaction was evaluated experimentally and theoretically. Abstract : Hydrogen-bridged bis(silylene) complexes of ruthenium and iron were synthesized as the first examples of this type containing Group 8 metals and their rare four-membered ring structures and multi-center bonding interactions at the M–Si–H–Si moiety were clarified by NMR spectroscopy, X-ray crystallography and theoretical calculations.